El uso virtuoso de la tecnología - Manzanero Fernández, Delia María (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
The science, seen like an activity, must have objectives and that way it can’t be neutral. The activity science have to make a question about their own objectives and moral assets. The development of science and technic, has the result of the dinamizacion of the moral. There are two opositive ideas. The first one, is the idea of the ethic’s imperative: "if you must, you can". And the second one, the opositive tecnology idea: "If you can, you must". It’s impossible to refuse the technology innovation. We have to be alert about the intrinsic inmorality of the tecnology. In way that the contemporany man follows the technic templates, he agrees the tecnology templates like an admisibles criteria of his moral actions. In this way, he loses his ethic’s contains. The present comunication analizes the use of the terminology of the word "virtus" presents in many authors, making a trayectory from the greece clasicism of Aristoteles, to the ilustrated spirit of Voltaire. They said that if you know the idea of the Good, then you are virtuous, but the facts in twenty century refuse this idea. One of the reasons is that in the twenty century the human being has left his mains moral principles. Well, but the main question is: Is technology good because it is required by society or, tecnology is in sociality because is necesary for the progress and, for this reason, is good?